MODIFIED METHODS FOR ESTIMATING THE QUALITY OF WHEAT GRAIN AGAINST THE BACKGROUND OF EXPOSURE TO SUNN PEST - E. N. Shabolkina; O. M. Sychyova; V. V. Syukov (Вавиловский журнал генетики и селекции)
It is demonstrated that modified micromethods of grain quality assessment can be applied to bread wheat against the background of sunn pest damage. It has been found that, that use of dilute solutions of organic acids in gluten quality assay with an IDK device and farinographic measurement of dough rheological properties reduces the paratypic noise caused by sunn pest.